2017
DOI: 10.1083/jcb.201706135
|View full text |Cite
|
Sign up to set email alerts
|

N-Glycan–dependent protein folding and endoplasmic reticulum retention regulate GPI-anchor processing

Abstract: N-Glycosylation and GPI anchoring of proteins occur in the endoplasmic reticulum (ER). Liu et al. revealed N-glycans participate in quality control and temporal ER retention of GPI-anchored proteins (GPI-APs), ensuring their correct folding and GPI processing before exiting from the ER. Chronic ER stress induced exposure of unprocessed GPI-APs on the cell surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 55 publications
(79 reference statements)
5
60
0
1
Order By: Relevance
“…Calnexin was observed to associate with CD59 in an N-glycan-and GPI-dependent manner (Figure S2 C), as previously observed (22). ERp57 weakly co-precipitated with CD59 and misfolded CD59, whereas interactions with other ER chaperones, such as calreticulin and BiP, were not detected with any CD59 construct (Figure S2 C), indicating that the N-glycan and membrane-associated domain of GPI-APs are important for calnexin interaction.…”
Section: Glycan Binding Of Calnexin Is Required For Efficient Gpi-inosupporting
confidence: 80%
See 3 more Smart Citations
“…Calnexin was observed to associate with CD59 in an N-glycan-and GPI-dependent manner (Figure S2 C), as previously observed (22). ERp57 weakly co-precipitated with CD59 and misfolded CD59, whereas interactions with other ER chaperones, such as calreticulin and BiP, were not detected with any CD59 construct (Figure S2 C), indicating that the N-glycan and membrane-associated domain of GPI-APs are important for calnexin interaction.…”
Section: Glycan Binding Of Calnexin Is Required For Efficient Gpi-inosupporting
confidence: 80%
“…If an acylchain is attached to the 2-position of the inositol, PI-PLC cannot cleave the substrate ( Figure 1A). We previously demonstrated that GPI-inositol deacylation of CD59 and CD55 is partially impaired in cells defective for calnexin (CANX) and is more strongly affected in cells defective for both CANX and calreticulin (CALR) (22). To determine if the CANX/CALR-dependency of GPI-inositol diacylation is a general phenomenon of various GPI-APs, we treated CANX&CALR-DKO HEK293 cells with PI-PLC, and endogenous CD59, CD55, and CD109 in the CANX&CALR-DKO cells showed PI-PLC resistance ( Figure 1B and C).…”
Section: Calnexin/calreticulin Cycle Is Required For Efficient Gpi-inmentioning
confidence: 99%
See 2 more Smart Citations
“…During the transport through the secretory pathway, misfolded GPI-APs are escorted by ER-derived chaperones, such as BiP and calnexin, and p24 proteins [116]. Most GPI-APs have at least one N-glycan and their folding is mediated by N-glycan-dependent calnexin cycle [117]. Calnexin also binds to PGAP1 and facilitates PGAP1-mediated removal of the acyl chain from inositol [117].…”
Section: Quality Control Of Gpi-apsmentioning
confidence: 99%